(untitled) (Research, Society and Development, 2019)
The Food and Nutrition Units (UANs) are establishments destined to the care of ... To ensure the quality of the food offered by a UAN, it must proceed in accordance with the principles of Good Food Handling Practices (BPMA). One of these principles is the precise maintenance and control of the temperatures of the food produced. The objective of this work was to verify the temperatures of the meals produced by a UAN from the beginning to the end of the distribution and to analyze possible failures and to discuss the importance of maintaining the temperatures to guarantee the safety of the food served by a UAN. A descriptive study with a quantitative approach was carried out at a UAN located in the municipality of Picos (PI) in 201 The temperatures of the hot and cold food were measured during the 30-day distribution stage at dinner time. The results were analyzed according to the temperatures recommended by RDC Resolution 216 of September 15, 2004 and CVS 5/2013. It can be seen that both cold and hot temperatures are inadequate, thus posing a risk to the health of the diners. However, it is important that stricter measures are taken in order to avoid problems for the integrity of food as well as the consumers of those meals.